Health information, what happens when there isn't any? Information literacy and the challenges for rare and orphan diseases. (September 2014) - Spring, Hannah
Abstract This feature looks at the challenges for information literacy in rare and orphan diseases. In particular, it focuses on the information difficulties faced by those living with a rare condition or awaiting a diagnosis, and also those of the health professionals in charge of their care. The feature also highlights some of the key issues that library and information professionals need to be aware of when providing information support in such circumstances. H.S.